A histological study of the medial meniscus posterior root tibial insertion. (1st November 2020) - Hino, Tomohito; Furumatsu, Takayuki; Miyazawa, Shinichi; Fujii, Masataka; Kodama, Yuya; Kamatsuki, Yusuke; Okazaki, Yoshiki; Masuda, Shin; Okazaki, Yuki; Ozaki, Toshifumi
ABSTRACT: Purpose/Aim of the study : Posterior root injury of the medial meniscus often leads to articular cartilage degeneration due to altered biomechanics. To avoid dysfunction, the attachment must be repaired using the transtibial pullout technique. To guide appropriate placement of the tibial tunnel, additional details on the normal anatomy of the meniscus insertion are needed. Therefore, we performed a histological analysis of a tibial bone slice with the medial meniscus posterior insertion obtained during total knee arthroplasty surgery. Materials and methods : Horizontal slices of the proximal tibia were obtained from 7 patients with osteoarthritis who underwent total knee arthroplasty. After decalcification, the region of the posterior horn was cut out and segmented into four pieces (2.0 mm thickness; medial to lateral). Sagittal sections were evaluated by safranin O staining or immunohistochemistry with anti-type collagen antibody. Results : Safranin O staining showed that the insertion of the posterior root consisted primarily of fibrocartilaginous layers in segment 2. Anatomically, segment 2 corresponded to the sagittal plane passing through the peak of the medial intercondylar tubercle. In this section, safranin O staining and immunohistochemistry revealed that the anterior one-third of the posterior root insertion was richer in proteoglycans and type II collagen than the central and posterior one-third. Conclusions : Anatomical insertion of the posterior root of the medial meniscus was located at the sagittal plane passing through the peak of the medial intercondylar tubercle. The structure of the medial meniscus posterior insertion was mainly localized in the anterior one-third.